Computation of Forced Premixed Flames Dynamics. Issue 7 (2nd July 2016) - Ruan, S.; Dunstan, T. D.; Swaminathan, N.; Balachandran, R.
ABSTRACT: Bluff body stabilized turbulent premixed flames subject to inlet velocity oscillation over a wide range of forcing frequency and amplitude are simulated using a flamelet-based combustion model. Two sets of detailed chemical kinetic schemes are used to model combustion chemistry. It is observed that the computed dynamics of forced flames agree reasonably well with experimental measurements. The flame elongation and shortening at a frequency of 40 Hz and strong flame-vortex interaction at a higher frequency of 160 Hz are captured well in the computations. The global flame describing function extracted from the computational results shows a linear response at 40 Hz and a nonlinear behavior at 160 Hz as observed in the experiments. The nonlinear response is due to vortex roll-up and its subsequent shedding. The quantitative agreement of the computed flame describing function (FDF) with experimental measurement is uniformly good over a wide range of forcing frequency and amplitude. Some influence of chemical kinetics on the FDFs is observed, which mainly stems from the difference in laminar burning velocity and spatial heat release rate distribution.